Potential of Ocimum basilicum L. and Salvia officinalis L. essential oils against biofilms of P. aeruginosa clinical isolates - Stojanović-radić, Z; Pejćić, M; Stojanović, N; Sharifi-Rad, J; Stanković, N (Cellular and Molecular Biology, 2016)
Biofilms are complex communities of microorganisms, responsible for more than 60% of the chronic human infections and they represent one of the leading concerns in medicine. Pseudomonas aeruginosa is human pathogenic bacteria which causes numerous diseases and is known for its ability to produce biofilm. Ocimum basilicum L. (basil) and Salvia officinalis L. (sage) are widely used plants in traditional medicine for the treatment of different conditions. Therefore, the aim of this study was to investigate the potential of basil and sage essential oils against P. aeruginosa biofilm producing strains. The efficacy of two essential oils on P. aeruginosa biofilm forming ability was determined using crystal violet method. Out of 15 strains isolated from different clinical biological samples, two were strong, 11 moderate and one weak biofilm producer. Good efficacy of sage essential oil towards strong and weak biofilm producers, but not of basil essential oil, was observed. In the case of moderate biofilm producers, 81.8% showed lower biofilm production after incubation with the sage oil, while 63.6% showed the reduction of biofilm production after basil essential oil treatment. The obtained results showed high potential of both oils for the treatment of persistent infections caused by Pseudomonas aeruginosa biofilms.